International political risk management : exploring new frontiers - Moran, Theodore H.; Multilateral Investment Guarantee Agency; World Bank. ([Washington, D.C.] : World Bank, 2001)
The purpose of this report is to present the ideas and experiences of some of the most distinguished practitioners from the investor, financial, and investment insurance communities in the world. To assist the reader, this volume's editor provides a brief overview to introduce each of the separate topics. Topics focus on the multiple pledge-of-shares problem; the preferred creditor status; breach of contract coverage in infrastructure projects, and OPIC modified expropriation coverage (using an Indonesian case study); securitizing political risk insurance; and cooperation, competition, and the "science of pricing" in the political risk insurance marketplace. The appendices also contain two articles: "Political Risk Investment Insurance: The Renaissance Revisited," and "Managing International Political Risk.
"This Working papers volume originated in a symposium on International Political Risk Management held on April 11, 2000, under the joint auspices of the Multilateral Investment Guarantee Agency of the World Bank Group and the Karl F. Landegger Program in International Business Diplomacy at the School of Foreign Service, Georgetown University"--Page viii.
oif 04/08/16
Loan
Keywords: Investment guaranty insurance; Risk (Insurance); Investments, Foreign; Country risk; Risk management; International business enterprises; Foreign direct investment